Implementasi Komunikasi Interpersonal KH Abdullah Syukri Zarkasyi Dalam Membentuk Karakter Santri Sebagai Kader Dakwah - Aini, Sofia Budi Andri (Program Studi Komunikasi dan Penyiaran Islam, Fakultas Dakwah, Institut Agama Islam Sunan Giri Ponorogo, 2024)
Each Islamic scholar (kyai) employs a unique interpersonal communication style when applying their leadership in their respective pesantren (Islamic boarding schools). This study aims to explore how KH Abdullah Syukri Zarkasyi implements interpersonal communication to create a systematic communication space within the pesantren, uncover the communication strategies used to shape the character of students (santri) as future Islamic propagators (dai), and examine how he preserves the tradition of effective communication in the pesantren setting. The theoretical framework employed in this research is the Fundamental Interpersonal Relationship Orientation (FIRO) Theory. This study adopts a constructivist paradigm and employs a qualitative descriptive research methodology. The subject of the research is KH Abdullah Syukri Zarkasyi. Data collection techniques involve a series of steps, including orientation and interviews, exploration and observation, and concluding with document analysis and review. KH Abdullah Syukri Zarkasyi establishes a relational communication space characterized by organized interactions that incorporate both verbal and non-verbal messages, conducted across various activities. The communication strategies employed are directly implemented through Guidance, Training, Task Assignment, Habit Formation, Supervision, and Exemplary Leadership (Uswatun Hasanah).This research contributes to understanding the role of interpersonal communication in Islamic education and leadership, highlighting its impact on fostering character development and maintaining a cohesive and effective pesantren culture